Applying patterns Pua Kumbu on ceramic lightings / Oskar Hasdinor Hassan, Rusmadiah Anwar and Noor Hasmida Mohd Khair - Hassan, Oskar Hasdinor; Anwar, Rusmadiah; Mohd Khair, Noor Hasmida (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Pua Kumbu is a valuable Iban textile. According to Iban belief each pattern has its own meaning and protected by spirit. It was used as functional items during ancient Iban spiritual ceremonies. In Sarawak crafts, Pua Kumbu motifs has been applied onto souvenir items such as bag and and table cloth. Some fashion designers and artist has been using Pua Kumbu as inspiration in their product design patterns, The objective of this innovation project is to apply the Pua Kumbu pattern in ceramic lighting, Finally, the patterns structure of Pua Kumbu which are engkaramba, flora and fauna were successfully applied on distinctive porcelain light.